THE USE OF TRADITIONAL GAME LAYANGAN SENDAREN AS A MEDIUM FOR LANGUAGE AND LITERATURE LEARNING TO ENHANCE LINGUISTIC SKILLS AND CULTURAL AWARENESS AT MI PLUS NURUL HUDA - Bhatti, Muhammad Safdar; Amalia, Anisa Nurul; Fahmi, Ahmad Zulfi; Ahyani, Hisam; Mutmainah, Naeli (Kantor Bahasa Kalimantan Timur, 2025)
This study explores the implementation of the traditional game layangan sendaren as a medium for language and literature learning at MI Plus Nurul Huda, an Islamic elementary school in Banjar City, Indonesia. The research focuses on three main problems: how the game is applied in the learning process, its impact on students’ language skills—especially vocabulary and oral literary expressions—and its role in preserving and enhancing students’ awareness of local Sundanese culture. Employing a qualitative ethnopedagogical approach, data were collected through classroom observations, interviews with teachers and students, and learning activity documentation. The findings reveal that layangan sendaren effectively increases student engagement, enriches vocabulary, and improves oral literary skills such as rhymes, metaphors, and proverbs. Additionally, the game plays a significant role in fostering cultural identity and appreciation by connecting students with their Sundanese heritage. This study suggests that integrating traditional cultural elements into language and literature education can enhance linguistic competence while promoting cultural preservation and character development in primary education contexts. Keywords: Traditional game, Language learning, Oral literature, Cultural awareness, Ethnopedagogy Abstrak Penelitian ini mengeksplorasi implementasi permainan tradisional layangan sendaren sebagai media pembelajaran bahasa dan sastra di MI Plus Nurul Huda, sebuah sekolah dasar Islam di Kota Banjar, Indonesia. Penelitian ini berfokus pada tiga permasalahan utama: bagaimana permainan ini diterapkan dalam proses pembelajaran, dampaknya terhadap keterampilan berbahasa siswa—terutama kosakata dan ekspresi sastra lisan—dan perannya dalam melestarikan dan meningkatkan kesadaran siswa terhadap budaya Sunda lokal. Dengan menggunakan pendekatan etnopedagogis kualitatif, data dikumpulkan melalui observasi kelas, wawancara dengan guru dan siswa, serta dokumentasi kegiatan pembelajaran. Temuan penelitian menunjukkan bahwa layangan sendaren efektif meningkatkan keterlibatan siswa, memperkaya kosakata, dan mengembangkan keterampilan sastra lisan seperti rima, metafora, dan peribahasa. Selain itu, permainan ini memainkan peran penting dalam menumbuhkan identitas dan apresiasi budaya dengan menghubungkan siswa dengan warisan Sunda mereka. Penelitian ini menunjukkan bahwa mengintegrasikan unsur-unsur budaya tradisional ke dalam pendidikan bahasa dan sastra dapat meningkatkan kompetensi linguistik sekaligus mendorong pelestarian budaya dan pengembangan karakter dalam konteks pendidikan dasar. Kata-kata Kunci: Permainan tradisional, Pembelajaran bahasa, Sastra lisan, Kesadaran budaya, Etnopedagogi